A special type of graphs of fractal curves with mathematica 11.0 - Correa Erazo, Segundo B. (2019)
In this article we generate graphs of fractal curves, which are determined as fixed points of a contractive operator. To do this, we consider five points P1; P2; P3; P4 y P5 in the plane and two affine transformations w1;w2, the same ones that will constitute a system of iterated functions (IFS) with only two contractive transformations. for the visualization of the graphs a program in mathematica 11.0 called fractalfunction has been created and we choose as the starting point of the iterative process the set [P1; P5]